PEGERAKAN KELOMPOK TERORISME DIKALANGAN UMMAT ISLAM (Suatu kajian dengan pendekatan Sejarah) - St. Aisyah Abbas (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
Terrorism is an ideology which argues that the use of means of violence, intimidation and the like that cause anxiety and fear, even the occurrence of loss of life and property, to achieve goals, either individually or in groups or in an organization, which has a wide network, both national and international scale. Academically, terrorism is categorized as an